Association Between Parenting and School Refusal Among Elementary School Children in Japan: Results From A-CHILD Longitudinal Study - Yoshifumi Fukuya; Takeo Fujiwara; Aya Isumi; Satomi Doi; Manami Ochi (Frontiers Media S.A., 2021)
Objective: The aim of this study was to examine the association between parenting, including the parent-child interaction and child maltreatment in the first grade (6-7 years old), and school refusal in the second (7-8 years old) and fourth (9-10 years old) grades among elementary school children in Japan.Methods: Data were from the Adachi Child Health Impact of Living Difficulty (A-CHILD) longitudinal study conducted in 2015, 2016, and 2018 in Adachi City, Tokyo, Japan. A questionnaire was distributed to all the first-grade school children (N = 5,355) in 2015. Of the total 4,291 valid children (response rate: 80.1%), 3,590 and 3,070 children were followed up to the second and fourth grades, respectively. Caregivers responded to the questionnaire on the parent-child interaction and child maltreatment, including neglect, physical abuse, and psychological abuse in the first grade and school refusal in the second and fourth grades. We conducted multiple imputation for missing data. Multivariate logistic regression model was used for this analysis adjusting for child mental health in the first grade and sociodemographic characteristics.Results: Prevalence of school refusal was 1.8% (n = 64) in the second grade and 2% (n = 60) in the fourth grade. We found no association of the parent-child interaction and child maltreatment in the first grade and with school refusal in the second and fourth grades, respectively, after adjusting for covariates.Conclusions: Parenting, such as the parent-child interaction and child maltreatment, may not be associated with school refusal among elementary school children. Further longitudinal research is needed to elucidate other factors, such as peer relationships and school environment, which can affect school refusal.